Regime Type and Political Destabilization in Cross-National Perspective: A Re-Analysis. (February 2017) - Slinko, Elena; Bilyuga, Stanislav; Zinkina, Julia; Korotayev, Andrey
In this article, we re-analyze the hypothesis that the relationship between the type of political regime and its political instability forms an inverted U shape. Following this logic, consistent democracies and autocracies are more stable regimes, whereas intermediate regimes (anocracies) display the lowest levels of political stability. We re-test this hypothesis using a data set that has not been previously used for this purpose, finding sufficient evidence to support the hypothesis pertaining to the aforementioned U-shaped relationship. Our analysis is specifically focused on the symmetry of this U shape, whereby our findings suggest that the U-shaped relationship between regime types and sociopolitical destabilization is typically characterized by an asymmetry, with consistently authoritarian regimes being generally less stable than consolidated democracies. We also find that the character of this asymmetry can change with time. In particular, our re-analysis suggests that U-shaped relationship experienced significant changes after the end of the Cold War. Before the end of the Cold War (1946-1991), the asymmetry of inverted U-shaped relationship was much less pronounced—though during this period consistent authoritarian regimes were already less stable than consolidated democracies, this very difference was only marginally significant. In the period that follows the end of the Cold War (1992-2014), this asymmetry underwent a substantial change: Consolidated democracies became significantly more stable, whereas consolidated autocracies became significantly more unstable. As a result, the asymmetry of the U-shaped relationship has become much more pronounced. The article discusses a number of factors that could account for this change.